Estudos teóricos e numéricos de escoamentos com escorregamento - Viezel, Caroline [UNESP] (2015)
In this work we present theoretical and numerical results by studying Newtonian and viscoelastic Poiseuille flow based on sPTT model (simplified Phan-Thien-Tanner ), considering a slip velocity on the wall described by the Navier-linear slip law. The theoretical study aims to expose an analytical solution for the problem mencioned above about incompressible and isothermal flow. The numerical contributions of this work is the extension of the methodology presented in [33] to flows under slip wall condition. In this extension, the flows are either Newtonian or viscoelastic fluids; however, an implementation has only been adapted and verified for confined flows. In the numerical studies will be presented a strategy for imposing the slip velocity on the wall, which depends on the derivative of the velocy and additionally, in the viscoelastic case, the shear component of the extra-stress tensor. Other small, but important, changes due to the wall slip condition will also be highlighted. In numeric context, the analytical solution will be used to verify the numerical implementation, what enables presenting the convergence analysis of the numerical solution to the analytical solution